Microbiota for production of wine with enhanced functional components - Armachius James; Ting Yao; Hengming Ke; Yousheng Wang (Food Science and Human Wellness)
Microbial communities during winemaking are diverse and change throughout the fermentation process. Microorganisms not only drive alcohol fermentation, flavor and aroma, but also enhance wine functional components such as extraction of polyphenols from the berries, production of γ-aminobutyric acid, hydroxytyrosol and melatonin. Polyphenols such as resveratrol, catechin and quercetin determine the functional quality of the wine. Moderate wine consumption, particularly red wine has been associated with functional benefits to human health, which includes anti-inflammation, promoting healthy aging, prevention of cardiovascular diseases, cancers, type 2 diabetes and metabolic syndrome. Indeed, the management of microbiota allows the production of wine with distinct features and functional components that benefits human health. This review scrutinizes the possible contributions of wine microbiota to the production of wine with enhanced functional components and highlights the contributions of Saccharomyces and non-Saccharomyces yeasts and bacteria to enhance wine functional components during winemaking. Thus, contributing to the dissemination of the benefits of light to moderate wine intake to human health.